Effect of transcranial direct current stimulation on visual perception function and performance capability of activities of daily living in stroke patients - Kim, Soo-Han; An, Tae-Gyu; Kim, Ko-Un (Journal of Physical Therapy Science, 2016)
[Purpose] The purpose of this study was to examine the effects of transcranial direct current stimulation (tDCS) on visual perception and performance of activities of daily living in patients with stroke. [Subjects and Methods] Thirty subjects were assigned equally to a tDCS plus traditional occupational therapy group (experimental group) and a traditional occupational therapy group (control group). The intervention was implemented five times per week, 30 minutes each, for six weeks. In order to assess visual perception function before and after the intervention, the motor-free visual perception test (MVPT) was conducted, and in order to compare the performance of activities of daily living, the Functional Independence Measure scale was employed. [Results] According to the results, both groups improved in visual perception function and in performance of activities of daily living. Although there was no significant difference between the two groups, the experimental group exhibited higher scores. [Conclusion] In conclusion, the application of tDCS for the rehabilitation of patients with stroke may positively affect their visual perception and ability to perform activities of daily living.